Rhabdomyolysis due to isoniazid poisoning resulting from the use of intramuscular pyridoxine - Eyüboğlu, Tuğba; Derinöz, Okşan (The Turkish Journal of Pediatrics, 2013)
Isoniazid is an effective antituberculosis drug. Isoniazid poisoning produces a characteristic clinical syndrome that occurs 30 to 120 minutes after ingestion and includes seizures, metabolic acidosis, and in severe cases, coma. Rhabdomyolysis is one of the reported complications of isoniazid poisoning, but relevant data are limited. Parenteral pyridoxine is the antidote of isoniazid. In this case, a 16-year-old male patient admitted to the Pediatric Emergency Department two hours after isoniazid poisoning. For treatment, intramuscular pyridoxine was used, but he developed serious rhabdomyolysis.